Natural Disasters Topic in Bahasa Learning Using Project-Based Learning (PJBL) - Armani Armani; Yanti Sudiarti; Widiantoro Dwi (Universitas Tanjungpura, 2023)
The aim of this study is to improve knowledge and understanding of Bahasa in natural disasters topic. The PJBL model was implemented with a quantitative descriptive research approachThe participants were 29 second-grade students at SDN 36 Pontianak. In Cycle 1, 21 students passed with a percentage of 72%, and those who have not passed amounted to 8 students with a percentage of 27%. In cycle II, with improved implementation with an accurate and targeted level using the PjBL Model, 29 students passed (100%). The existence of the PjBL model and understanding of natural disasters can be accepted because the students are given a wide opportunity to conduct smaller and more effective group discussions.